Factores que determinan el uso de las TIC en adultos mayores de Chile - Aguilar-Flores, Sandra Marlene; Margaret Mary (Revista Científica, 2020)
The objective of this study is to determine the factors of the use of information technologies in older adults in the province of Concepción, Chile, based on the model The Unified Theory of Adoption and Use of Technology (UTAUT). The study was carried out on the population of 101 older adults, for the analysis of the data and to check the hypotheses, a model of structural equations has been estimated. The proposed relationships, using latent variables, help to explain the Use of information technologies by 55% in older adults. To reduce the digital divide, it can be concluded that there are factors that positively determine the use of ICT, which makes it easier for them to have optimal access, thus improving their quality of life and real digital integration.